Undernutrition and associated factors among pregnant women in Ethiopia. A systematic review and meta-analysis - Zewude, Shimeles Biru; Beshah, Mekonen Haile; Ahunie, Mengesha Assefa; Arega, Dawit Tiruneh; Addisu, Dagne (Frontiers in Nutrition, 2024)
Background Maternal undernutrition is a major public health concern due to its association with mortality and overall disease burden for mothers and their children. Maternal nutrition determines pregnancy outcomes since reduced intake of nutrients influences gestational age length, placental function, and fetal growth during pregnancy. The complexity of the intergenerational aspects of maternal nutrition may also confound the design of interventions. Therefore, this research aimed to assess the prevalence of undernutrition and associated factors among pregnant women in Ethiopia. Methods We identified the literature from PubMed, EMBASE, Scopus, and CINAHL databases. Data were entered into Microsoft Excel and then exported to Stata version 17 statistical software for analysis. The I2 and Q-statistic values detect the level of heterogeneity, and meta regression was performed to investigate between-study heterogeneity using more than one moderator. JBI quality assessment tools were used to include relevant articles. Evidence of publication bias was indicated using the funnel plot and Egger's linear regression test. The effect size was expressed in the form of point estimates and an odds ratio of 95% CI in the fixed-effect model. Result In total, 19 studies fulfill the inclusion criteria. The pooled prevalence of undernutrition among pregnant women was 32% (95% CI 31.3–33.2 I2 = 97.5%, P < 0.0). Illiteracy (AOR = 3.6 95% CI; 2.3–5.6), rural residence (AOR = 2.6 95% CI; 1.2–3.5), a lack of prenatal dietary advice (AOR = 2.6 95% CI; 1.8–3.7), household food insecurity (AOR = 2.5 95% CI; 1.9–3.2), and low dietary diversity score (AOR = 3.7 95% CI; 2.2–5.9) appear to be significantly associated with undernutrition among pregnant women. Conclusion The review showed that the prevalence of undernutrition is still high among pregnant women. Illiteracy, rural residence, a lack of prenatal dietary advice, household food insecurity, and low dietary diversity score were significantly associated with undernutrition during pregnancy. Interventions should focus on educating the public and helping families access food or supplements they need through local markets, health systems, and community-based support, as undernutrition is caused by numerous interconnected causes. Systematic review registration https://www.crd.york.ac.uk/prospero/#myprospero, identifier: CRD42023417028.